Rola dramy i technik dramowych w kształceniu umiejętności lekturowych - Motyka, Agnieszka (Dydaktyka Polonistyczna, 2020)
The article shows that the drama and staging techniques have a multi-dimensional effect onprimary school students’ versatile development. The author – Polish language teacher in a primaryschool – presents the examples of the usage of drama during the lesson and their benefits.